Sex as a Moderating Factor in the Relationship Between Hippocampal Volume and Sensory Gating in Patients With Schizophrenia. (July 2019) - Huang, Wei-Lieh; Liu, Chao-Yu; Liu, Hon-Man; Liu, Chih-Min; Hsieh, Ming H.
Building on the knowledge of sex differences in auditory sensory gating in schizophrenia and hippocampal involvement in sensory gating, this study aimed to investigate sex as a potential moderator of the association between hippocampal volume and P50 in schizophrenia. Auditory P50 gating and hippocampal volume were measured in 16 male and 15 female patients with schizophrenia. The correlations between hippocampal volume and P50 were analyzed in males and females separately, corrected for potential confounders, including age, duration of illness, and antipsychotic medication. Different associative patterns of hippocampal volume with P50 gating ratio and with P50 difference were found by sex. The results suggest sex may play a role in the physiology of sensory gating.